Feasibility and Safety of Field-Based Physical Fitness Tests: A Systematic Review - Carolina Cruz-León; Pablo Expósito-Carrillo; Sandra Sánchez-Parente; José Jiménez-Iglesias; Milkana Borges-Cosic; Magdalena Cuenca-Garcia; José Castro-Piñero (Sports Medicine - Open)
Abstract Background While there is evidence on the validity and reliability of field-based physical fitness tests in children, adolescents and adults, there is limited evidence to provide feasibility and safety data on the application and performance of the existing field-based physical fitness tests. Objectives (i) To examine the feasibility and safety of existing field-based physical fitness tests used in people of all ages and (ii) to establish a comprehensive view of criterion-related validity, reliability, feasibility and safety based on scientific evidence for the existing field-based physical fitness tests in adults. Methods The search was conducted through the electronic databases MEDLINE (via PubMed) and Web of Science (all databases) for published studies from inception to 31 January 2023. This systematic review was developed according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Studies were classified as very low quality, low quality or high quality, based on the criteria of appropriate number of participants, appropriate description of the study population, and appropriate number of items reported to assess feasibility/safety. Three evidence levels were constructed (strong, moderate and limited or inconclusive evidence) according to the number of studies and the consistency of the findings. Results We identified a total of 19 (14 of high quality) and 13 (11 high quality) original studies examining the feasibility and safety of field-based physical fitness tests, respectively. Strong evidence indicated that (a) the 2-km walk and 20-m shuttle run tests were feasible in adults and, children and adolescents, respectively; (b) the handgrip strength test was feasible in children and adolescents; and (c) the standing long jump test was feasible in children and adolescents. Only the 2-km walk test has shown strong evidence on safety in adults. Finally, combining the levels of evidence of criterion-related validity, reliability, feasibility and safety in adults, all the field-based physical fitness tests show limited evidence. Conclusion There is a need for more studies and consensus to establish homogeneous methodological criteria to assess the feasibility and safety of field-based fitness tests. The combined evidence on criterion-related validity, reliability, feasibility and safety of field-based tests was found to be limited in adults. PROSPERO reference number CRD42022298276.